Gastrophysics the new science of eating - Spence, Charles 1969- (Penguin Books, 2018)
Why do we consume 35% more food when eating with one more person, and 75% more when with three? Why are 27% of drinks bought on aeroplanes tomato juice? How are chefs and companies planning to transform our dining experiences, and what can we learn from their cutting-edge insights to make memorable meals at home? These are just some of the ingredients of Gastrophysics, in which the pioneering Oxford professor Charles Spence shows how our senses link up in the most extraordinary ways, and reveals the importance of all the "off-the-plate" elements of a meal: the weight of cutlery, the colour of the plate (his lab showed that red is associated with sweetness - we perceive salty popcorn as tasting sweet when served in a red bowl), the background music and much more. Whether dining alone or at a dinner party, on a plane or in front of the TV, he reveals how to understand what we're tasting and influence what others experience. Meal-times will genuinely never be the same again
First published in Great Britain by Viking, an imprint of Penguin Random House UK, 2017. - Includes bibliographical references (pages 267-292) and index
Keywords: Sensorik -- Neurophysiologie; Wissenschaft; Gastrosophie; Nahrungsaufnahme; Gastronomy; Food / Sensory evaluation; Dinners and dining; Nutrition